Extreme chemical abundance ratio suggesting an exotic origin for an ultradiffuse galaxy - Martín-Navarro, Ignacio; Martínez-Delgado, David (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Ultradiffuse galaxies (UDGs) are a population of extended galaxies but with relatively low luminosities. The origin of these objects remains unclear,